Challenges in pediatric nursing: A global and Nepalese perspective - Anuja Kachapati; Sigma Bhattarai; Srishti Rawal; Bhagawati Thapa; Sharmila Bhandari; Kavita Lamichhane; Nagendra Chaudhary (Journal of Universal College of Medical Sciences, 2026)
Pediatric nursing is a specialized field that requires not only strong clinical competence but also patience and emotional resilience. It focuses on the care of infants, children, and adolescents, where involvement of the family involvement plays a crucial role in the overall care process. Despite advancements in healthcare systems across many parts of the world, pediatric nurses continue to encounter several challenges that influence the quality and delivery of care. At the global level, common issues include a shortage of nursing staffs, increased workload, and the need to adapt to rapidly evolving technologies. In Nepal, these challenges are further intensified by limited resources, difficult geographical conditions, and restricted access to specialized training opportunities. This review therefore examines both global and Nepalese contexts to better understand the existing challenges in pediatric nursing and to identify key areas requiring improvement.